KONTRIBUSI KOMITMEN GURU PADA TUGAS DAN KOMUNIKASI INTERPERSONAL SECARA BERSAMA-SAMA TERHADAP IKLIM KERJA SAMA GURU SD NEGERI DI KECAMATAN JAYA BARU KOTA BANDA ACEH - Nurhaidah M Insya Musa; Alfiati Syafrina (Universitas Syiah Kuala, 2021)
The aim of this research was to investigate the contribution of teacher's commitment to interpersonal task and communication toward state elementary school teachers collaborations at Jaya Baru sub-district, city of Banda Aceh. There were 26 respondents of elementary school teachers at Jaya Baru sub-district, Banda Aceh. The results of this research showed that: (1) there is a relationship between commitment (X1) and Y which is significant with the correlation value of 0.635. It showed that commitment has good relationship with collaboration of teacher, (2) the relationship between interpersonal communication (X2) and Y were significant with the correlation value of 0 .535. It showed that interpersonal communication have normal relationship with teacher's collaboration, and (3) Relationship between interpersonal commitment and communication with teacher's collaboration is as big as 0.728. In other words, the relationship between the organization and capability 100% have not met yet requisite of being professionally teacher and to create the collaboration sphere which it should be. It also means that their collaboration is not complete yet so that it needs to be increased in the future in order to get better quality for elementary schools at Jaya Baru sub-district, city of Banda Aceh.